Ergonomic Reliability Assessment for Operation Process of Medical Device Interface Design Based on OAT and CREAM. Issue 4 (January 2021) - Liu, Xin; Liu, Zheng; Xie, Ziyu; Chen, Pengqing
Abstract: This paper uses OAT (Operator Action Tree) and CREAM (Cognitive Reliability and Error Analysis Method) to analyze the interface design of medical equipment according to human error, discuss how to accurately describe the operator's failure behavior, determine the development sequence of important human factors events and the feasible calculation method according to the system response, establish a complete ergonomic reliability assessment modeling by example demonstrations. This study can better describe the relationship between software interface reliability and ergonomic reliability. In addition, this paper makes improvement on the cognitive reliability and error analysis. In this paper, based on the basic concept and core idea of CREAM method, MADM (Multi-attribute Decision-making) is used to improve the weighting factor value of CPCs (Common Performance Conditions) provided by CREAM method. After the OAT model building based on the operation process of medical device interface design, the adjusted failure probability prediction analysis method is applied to obtain the failure probability of OAT basic events, which makes CREAM method more suitable for the medical device accident analysis and risk assessment in complex environment.